Nonlinear optical absorption and optical rectification in near-surface double quantum wells: combined effects of electric, magnetic fields and hydrostatic pressure (2012)
ABSTRACT: The theoretical study of the combined effects of electric and magnetic fields and hydrostatic pressure on the nonlinear optical absorption and rectification is presented for electrons confined within an asymmetrical GaAs-Ga1−xAlx As double quantum well. The effective mass, parabolic band, and envelope function approaches are used as tools for the investigation. The electric field is taken to be oriented along the growth direction of the heterostructure and the magnetic field is applied parallel to the interfaces of the quantum wells. The pressure-induced mixing between the two lowest conduction bands is considered both in the low and high pressure regimes. According to the results obtained it can be concluded that the nonlinear optical absorption and rectification coefficients depend in a non-trivial way on some internal and external parameters such as the size of the quantum wells, the direction of applied electric field, the magnitude of hydrostatic pressure, the stoichiometry of the wells and barriers, and the intensity of the applied magnetic field.